Professional Identity of Long - Service Teachers: Continuing to Flourish in the Face of Change/Disseration Submitted to the University of Derby in Partial Fulfilment of the Requirements for the Degree of Master of Arts in Education - Corry Adele; Triantafyllaki Angeliki (2020)
Introduction, Structure of the Thesis, Research Focus, Literature Review, Introduction, Long - Service Teachers, Teachers' Professional Identity, Influences on Identity, Tensions and Challenges, Commitment and Motivation and Job Satisfaction, Leadership, Conclusion, Methodology, Theoretical Position, Methodological Approach, Data Collection Tool, Sampling Strategy, Researcher Involvement and Bias, Data Collection Tool, Sampling Strategy, Researcher Involvement and Bias, Data Collection Process, Validity and Reliability, Ethics, Data Analysis, Limitations, Coclusion, References.